Implementation Of The 4f Learning Model (Fact, Feeling, Finding, And Future) To Improve Students' Descriptive Text Writing Skills - Widi Wiliyarse; Ida Ayu Made Wedasuwari; Ni Luh Sukanadi (Journal of Educational Management Research, 2026)
This study aims to improve the descriptive text writing skills of seventh-grade students through the implementation of the 4F learning model (Fact, Feeling, Finding, and Future). The research employed Classroom Action Research (CAR) conducted in two cycles, with data collected through observation, writing tests, documentation, and questionnaires. The data were analyzed using descriptive qualitative and quantitative techniques to measure both the learning process and students’ writing achievement. The results indicate a significant improvement in students’ average scores, increasing from 49.48 in the pre-test to 65.28 in Cycle I and 86.02 in Cycle II. The structured stages of the 4F model observing facts, expressing feelings, identifying findings, and formulating future expectations effectively guided students in organizing ideas into coherent descriptive texts, supported by audiovisual and visual media. Students also demonstrated highly positive responses, with an approval rate of 98.96%. These findings imply that the 4F learning model can serve as an effective and engaging instructional strategy to enhance students’ descriptive writing skills at the junior secondary level.